Randomized Controlled Trial of Adjunctive Social Cognition and Interaction Training, Adjunctive Therapeutic Alliance Focused Therapy, and Treatment As Usual Among Persons With Serious Mental Illness - Hasson-Ohayon, Ilanit; Mashiach-Eizenberg, Michal; Lavi-Rotenberg, Adi; Roe, David (Frontiers in Psychiatry, 2019)
As one of the areas of greatest concern for people with serious mental illness (SMI) are unmet social needs, psychosocial interventions have been developed to address them. The current study utilized a randomized controlled trial to examine the effectiveness of social cognition and interaction training (SCIT) versus a therapeutic alliance focused theraphy (TAFT) versus a treatment-as-usual (TAU) control group on social functioning and quality of life as primary outcomes and social cognition variables as secondary outcomes. Sixty-three persons between the ages of 24 and 69 years with SMI (41 men and 22 women), completers of the trial (23 in SCIT, 20 in TAFT, and 20 in TAU), were assessed at baseline, completion, and at a 3-month follow-up with measurements assessing social cognition (The Facial Emotion Identification Task, The Faux pas test, The Ambiguous Intentions Hostility Questionnaire) social functioning, (The Social Skills Performance Assessment, The Wisconsin Social Quality of Life Scale), and therapeutic alliance (adapted version for group of system for observing family therapy alliance). Results reveal that the two interventions were more effective than the control condition (TAU) in reducing attribution bias anger scores, SCIT was also effective in improving theory of mind (as can be seen in Faux pas test scores), and the TAFT in improving emotion recognition and reducing intentionality attribution bias scores. Improvement was related to therapeutic alliance which did not differ between the two intervention groups. Considering the role of alliance, it is recommended to consider the integration of the two studied interventions with other approaches that emphasize alliance and reflection. Clinical Trial Registration:www.ClinicalTrials.gov, identifier NCT02380885.